2022
DOI: 10.1017/s0890060421000408
|View full text |Cite
|
Sign up to set email alerts
|

Potentials and challenges of analyzing use phase data in product planning of manufacturing companies

Abstract: The successful planning of future product generations requires reliable insights into the actual products’ problems and potentials for improvement. A valuable source for these insights is the product use phase. In practice, product planners are often forced to work with assumptions and speculations as insights from the use phase are insufficiently identified and documented. A new opportunity to address this problem arises from the ongoing digitalization that enables products to generate and collect data during… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 28 publications
0
2
0
Order By: Relevance
“…Two studies on DDD for product portfolio planning are identified, which are conducted by the same scholars (Meyer et al, 2021(Meyer et al, : 2022. The scholars argue that even if product planning and data analytics are two established and independent research areas and together, they span the new research areas, research on this topic is absent.…”
Section: Product Portfolio Planningmentioning
confidence: 99%
“…Two studies on DDD for product portfolio planning are identified, which are conducted by the same scholars (Meyer et al, 2021(Meyer et al, : 2022. The scholars argue that even if product planning and data analytics are two established and independent research areas and together, they span the new research areas, research on this topic is absent.…”
Section: Product Portfolio Planningmentioning
confidence: 99%
“…It was also determined that current DDPD studies could outperform classical design methods in well-de ned tasks, but still cannot master creative/innovative design tasks that require cognitive ability. Meyer et al [12] present 17 use cases that provide an overview of the possibilities offered by data analysis in product planning, reiterate the importance of data analysis, and point out that this topic is relatively new to many manufacturing companies and that many of these have little experience and/or expertise in this eld [13]. Meyer et al [14] offered practitioners a number and variety of investigations that can be performed with data in the use phases and at the end emphasizes that empirical research on this topic should gain even more importance.…”
Section: Introductionmentioning
confidence: 99%